2007
DOI: 10.1161/circresaha.107.155721
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy to Inhibit the Calcium Channel β Subunit

Abstract: Abstract-CalciumKey Words: hypertrophy Ⅲ calcium Ⅲ gene therapy C alcium cycling in the heart is triggered by calcium influx through L-type calcium channels. 1 Such calcium channels are present and functionally important not only in cardiac myocytes but also in diverse smooth muscles and in neurons. Enhancement of calcium-regulated signaling pathways contributes to the development of left ventricular hypertrophy (LVH). 2 Thus, calcium channel inhibition represents a logical approach to treatment of LVH. Gene t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 39 publications
0
20
1
Order By: Relevance
“…Several evidences suggest that alterations in Ca V ␤ 2 underlie some forms of myocardial dysfunction (61)(62)(63)(64), and so far, gene therapy to inhibit Ca V ␤ 2 has been considered only in correlation to an electrophysiological phenotype (65). …”
Section: Discussionmentioning
confidence: 99%
“…Several evidences suggest that alterations in Ca V ␤ 2 underlie some forms of myocardial dysfunction (61)(62)(63)(64), and so far, gene therapy to inhibit Ca V ␤ 2 has been considered only in correlation to an electrophysiological phenotype (65). …”
Section: Discussionmentioning
confidence: 99%
“…The L-type Ca 2ϩ current (L-current) density was similar in sham-operated WT myocytes compared Figure 7C). It has been reported that the reduction of the L-current by continuous infusion of L-channel blocker 35 or the knockdown of L-channel accessory ␤ subunit 36 channels that open at the resting membrane potential of a HEK293 cell (ie, window current). 37,38 As shown in Figure 8A, 10 mmol/L Ca 2ϩ significantly increased the NFAT-luciferase reporter activity relative to that of cells transfected with control vehicle and T-channel blocker mibefradil effectively blocked NFAT-luciferase activity triggered by calcium.…”
Section: Currents From Acutely Isolated Left Ventricular Myocytesmentioning
confidence: 99%
“…In addition, mice with cardiac myocyte-specific NOS3 overexpression had limited hypertrophy and contractile dysfunction after pressure overload and myocardial infarction (10,23). Furthermore, it is known that I Ca plays a role in hypertrophy (14). Ca 2ϩ influx via I Ca activates calcineurin, leading to nuclear factor of activated T cells dephosphorylation and the activation of hypertrophic signaling.…”
Section: Nos3 and Arrhythmogenesismentioning
confidence: 99%